Epigallocatechin Gallate Adjuvant Immunomodulatory Therapy for Hypersensitivity Pneumonitis - Ray , Roshmi; Venkatachalam , V. V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The current research aims to investigate the management of Hypersensitivity Pneumonitis (HP), a respiratory ailment affecting the lung parenchyma, particularly the alveoli, terminal bronchioli, and alveolar interstitium, due to a delayed allergic response. Various factors, such as microbial agents, animal and plant proteins, organic and inorganic compounds, and environmental substances, can contribute to respiratory issues. The inflammatory reaction in the alveolar mucosa is a hypersensitive response of type-3 (immune-complex-mediated) or type-4 (T-lymphocytes-mediated) that plays a role in the development of HP. Depending on the frequency and intensity of exposure to the causative antigens, the disease is categorized into acute, subacute, and chronic forms. The research shows the success for subacute and chronic forms of the disease as an alternative to corticosteroids. Although corticosteroids can provide relief for subacute and chronic HP as well as acute symptoms, they do not appear to alter the disease's long-term progression. As corticosteroids are only suitable for certain patients, there is a pressing need for an alternative treatment option to advance patient care. Sea Buckthorn is known to exhibit various beneficial effects, such as antioxidative, cytoprotective, wound-healing, immunomodulatory, and cardioprotective properties, among others. In contrast, Epigallocatechin gallate (EGCG) possesses antioxidant properties and can also mitigate the production of inflammatory cytokines, which are responsible for inducing inflammation in the body. The study postulates that incorporating EGCG alongside deciduous plant extracts could serve as a supplementary agent for HP treatment. Consequently, the research confirms the efficacy of the test medications in managing HP. It is essential to continue exploring alternative treatments and novel therapies to address the multifaceted aspects of HP and improve patients' overall quality of life. By broadening our understanding of the disease and potential treatment approaches, medical professionals can develop more personalized and effective interventions tailored to each patient's needs. Further investigations into the interplay between various therapeutic agents and their mechanisms of action will undoubtedly pave the way for more advanced and comprehensive strategies for combating HP. The study focuses on the Toluene di-isocyanate induced Hypersensitivity Pneumonitis rats with the prophylactic as well as therapeutic dose of the Sea Buckthorn berries extract along with the Epigallocatechin gallate for around 2.5 months. The paper also shows the various parameters on which the research has been successfully conducted. The research confirms the effectiveness of the test medications in modern HP treatment. This gives a basis for replacing the steroid therapy and opt for the better prolonged lifestyle.